2012
DOI: 10.1177/1533317512467680
|View full text |Cite|
|
Sign up to set email alerts
|

Histone Deacetylases Enzyme, Copper, and IL-8 Levels in Patients With Alzheimer’s Disease

Abstract: Plasma levels of HDACs and copper may be used as peripheral biomarkers in diagnosis of AD, while IL-8 level could be a useful biomarker in following AD progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 46 publications
(76 reference statements)
2
34
0
Order By: Relevance
“…IL-8 has been known to initiate acute inflammation, and our data support the involvement of elevated IL-8 in the chronic neuroinflammation of AD which may be related to cerebrovascular damage [30]. Actually, significant elevations in plasma IL-8 levels in cognitive impairment have also been reported by others [5,13], although there are also conflicting data showing lower IL-8 level in mild cognitive impairment and AD [31]. The mechanism underlying associations of IL-8 with WMH is at present unclear.…”
Section: Discussionsupporting
confidence: 88%
“…IL-8 has been known to initiate acute inflammation, and our data support the involvement of elevated IL-8 in the chronic neuroinflammation of AD which may be related to cerebrovascular damage [30]. Actually, significant elevations in plasma IL-8 levels in cognitive impairment have also been reported by others [5,13], although there are also conflicting data showing lower IL-8 level in mild cognitive impairment and AD [31]. The mechanism underlying associations of IL-8 with WMH is at present unclear.…”
Section: Discussionsupporting
confidence: 88%
“…Changes in levels of IL-6, IL-8, IL-12, and TNFα have been reported. Similar changes are observed in AD (Singh and Guthikonda, 1997; Swardfager et al, 2010; Cojocaru et al, 2011; Alsadany et al, 2013). While a lack of data exists regarding MyD88 in human AD patients, in one AD mouse model genetic ablation of MyD88 was found to mitigate microglial activation and amyloid beta toxicity (Lim et al, 2011).…”
Section: Sterile Inflammationsupporting
confidence: 64%
“…The results showed that levels of IL-8 and monocyte chemo-attractant protein 1 (MCP-1) were significantly increased in brain tissue derived from AD patients relative to controls. A more recent work has also reported that levels of IL-8 were considerably elevated in AD patients compared to non-demented controls [12]. Importantly, the increased levels of IL-8 showed a correlation with a reduced performance on cell cognition tasks.…”
Section: Introductionmentioning
confidence: 84%